Pembinaan Karakter Peserta Didik Melalui Kegiatan Kultum Di SMP Negeri 2 Kecamatan Medang Deras - Sahpitri, Dita Yuliana (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research is entitled "Students' Character Building Through Cultural Activities at SMP Negeri 2 Medang Deras District". The aim of this research is to find out how to develop the character and discipline of students through cultural activities. This research uses qualitative methods with field research. The techniques used to obtain data are interviews, observation and documentation. Meanwhile, the data analysis technique used in this research uses the Miles and Huberman data analysis model, which consists of several steps, namely: 1) Collecting data; 2) Data reduction; 3) Data display; 4) Drawing conclusions and verifying data. Meanwhile, the technique for ensuring the validity of the data used in this research uses triangulation, both source, technique and time triangulation. . To form character in students is done through treatment accompanied by awareness in students. The character formation process is carried out through several stages or processes in forming the disciplined character of students. The character emphasized in this research focuses more on the formation of disciplined character in students, which is a form of disciplined personality for students as a form of awareness, obedience to rules and self-control.